Characterization of the venom of C. d. cumanesis of Colombia: Proteomic analysis and antivenomic study (2023)
The Colombian rattlesnake Crotalus durissus cumanensis is distributed in three geographic zones of the country: the Atlantic Coast, the upper valley of the Magdalena River, and the eastern plains of the Colombian Orinoquía. Its venom induces neurological symptoms, such as eyelid ptosis, myasthenic facies, and paralysis of the respiratory muscles, which can lead to death. Identification and analysis of C. d. cumanensis showed nine groups of proteins responsible for the neurotoxic effect, of which the crotoxin complex was the most abundant (64.71%). Immunorecognition tests of C. d. cumanensis showed that the use of a commercial antivenom manufactured in Mexico resulted in immunoreactivity. © 2018 by the authors.